SUPERVISORY FUNCTION OF THE TOURISM OFFICE IN THE DEVELOPMENT OF THE GUNUNG SITU SUSPENSION BRIDGE AREA - Alvhi Vhidini Apriliani; Dine Meigawati; M. Rijal Amirulloh (DIA: Jurnal Administrasi Publik, 2023)
This study aims to determine the management of the Sukabumi Regency Tourism Office in the function of supervising the development of The Situ Gunung Suspension Bridge tourist area in the implementation of tourism implementation in Sukabumi Regency carried out by the Sukabumi Regency Regional Government through the Tourism Office has been regulated in the Peraturan Bupati Sukabumi Nomor 105 Tahun 2018 concerning the organizational structure and, communities and people around the area. Research using Terry and Rue theory (2019). The research method uses descriptive method with qualitative approach. Data collection using observation techniques, interviews, documentation, and combined/triangulation. Validation data using triangulation techniques and data analysis using data reduction, data presentation, and drawing conclusions. The results of this study show that the supervisory function carried out by the department in the development of The Situ Gunung Suspension Bridge tourist destination area is running well looking at the theoretical dimensions of Planning, Organizing, Staffing, Motivating, and Controlling according to Terry and Rue (2019).